Poland's Refugee Policy and Polish Society Between Values of Survival and Self-Expression - Elżbieta Wiącek (Ksiegarnia Akademicka Publishing, 2017)
At the beginning of November 2015, the Polish government’s decision to accept 6,800 refugees fleeing Syria and Eritrea created a fierce debate dividing Polish society. A poll conducted by the Polish Research Centre found that twothirds of Poles oppose taking in refugees from the Middle East and North Africa. Thousands of protesters and counter-protesters gathered on the streets. It is difficult to draw the line dividing the pro-refugee Poles and those who are opposed to taking them in. This line does not run between political leaders and “ordinary” citizens as, in both groups, one can find a variety of attitudes. One of the major factors behind anti-migrant views is Poland’s religious and ethnic homogeneity. This present state of affairs differs radically from the multinational, multicultural state of Poland as it existed up to the Second World War. Between the 15th and 17th centuries, while Europe was absorbed with religious turmoil, Poland was famous for religious tolerance and for being a sanctuary for many refugees escaping from persecution. Thus, have the Poles lost their spirit of tolerance and hospitality?